PENGARUH VARIABEL MAKRO EKONOMI DAN HARGA MINYAK DUNIA TERHADAP INDUSTRI HALAL - Ali Mahdy Arrosikh; Ilmiawan Auwalin (Jurnal Ekonomi Syariah Teori dan Terapan, 2019)
This paper aims to discover the influence of inflation rate, exchange rate, global’s oil price and FDI toward halal industry in 48 OIC’s member Countries. This research uses data by Statistical, Economic and Social Research and Training Centre for Islamic Countries (Sesric), world bank and Thomas Reuters with quantative approach and were analyzed by using panel data analysis. According to the result it is have positive significant influence to the halal industry in 48 OIC Countries. Inflation rate have a significant positive influant; exchange rate have a non significant positive influant; global’s oil price have a significant negative influant; and FDI have a non-significant negative influant toward the increasing of the unemployment rate in 48 OIC’s Countries.Keywords: Halal Industry, Inflation, Exchange Rate, Global’s Oil Price, FDIREFFERENCESAbdullah, Boedi, & Saebani, Beni Ahmad. 2014. Metode Penelitian Ekonomi Islam. Bandung: Pustaka Setia.Arsyad, Lincolin. 2010. Ekonomi Pembangunan. Yogyakarta: UPP STIM YKPN.Aziz, Yuhanis Abdul & Nyen Yui Chok. 2012. "The Role of Halal Awareness, Halal Certification, and Marketing Components in Determining Halal Purchase Intention among Non-Muslims in Malaysia: A Structural Equation Modeling Approach". Journal of International Food & Agribusiness Marketing, 25:1-23.Arif. 2014. Metode Penelitian. Medan: Universitas Negeri Medan.Chapra, M. Umer, 1992. Islam and Economic Challange. The Islamic Foundation and International Institute of Islamic Thought, London and Herndon. Cologni, A and M. Manera. (2008). Oil Prices, Inflation and Interest Rates in a Structural Cointegrated VAR Model for the G-7 Countries. Energy Economics  (30). pp. 856–888.Doğrul, H. G. and U. Soytas. (2010). Relationship between Oil Prices, Interest Rate, and Unemployment: Evidence from an Emerging Market. Energy Economics  (32), pp. 1523– 1528.Elasrag, Hussein. 2016. Halal Industri: Key Challanges and Opportunities. Munich Personal RePec ArchiveGillman, Max, and Anton Nakov, 2003, A Revised Tobin Effect from Inflation: Relatif Input Price and Capital Ratio Realignments, US and UK, 1959-1999, Economica Vol 70 No. 279 (August 2003Gokal, Vikesh and Subrina Hanif (2004), Relationship Between Inflation and Economic Growth, Bank Of Fiji, Working Paper.Gujarati, Damodar N.1991. Ekonometrika Dasar Edisi Ketiga Terjemahan. Jakarta : Erlangga.Hailu, Z.H. (2010). Impact of Foreign Direct Investment on Trade of African Countries. International Journal of Economics and Finance Vol. 2, No. 3; August 2010. www.ccsenet.org/ijef.Huda, Nurul dkk. 2008. Ekonomi Makro Islam: Pendekatan Teoritis. Edisi Pertama. Jakarta : Kencana Prenada Media GrupKamali, Mohammad Hashim. 2013. The Parameters of Halal and Haram in Shariah and the Halal Industri. London : The International Institute of Islamic ThoughtMIFC. 2015. Halal Ecosystem Prospects for Global Growth. Malaysia : MIFCMukhtar, A. And Butt, M.M. (2012), “Intention to choose Halal products: the role of religiosity”, Journal of Islamic Marketing, Vol. 3 No. 2, pp. 108-120.P3EI. 2012. Ekonomi Islam. Jakarta: PT. Raja Grafindo PersadaSadorsky, P. (1999). Oil Price Shocks and Stock Market Activity. Energy Economics (21), pp. 449 – 469.Tang, W; L.Wu, Libo and Z.X. Zhang. (2010). Oil Price Shocks and their Short- and Long-Term Effects on the Chinese Economy. Energy Economics  (32), pp. S3–S14.Thomson Reuters. 2013. State of The Global Islamic Economy 2013 Report. Dubai : Thomson Reuters______________. 2014. State of The Global Islamic Economy 2014/2015 Report. Dubai : Thomson Reuters.______________. 2015. State of The Global Islamic Economy 2015/2016 Report. Dubai : Thomson Reuters.______________. 2016. State of The Global Islamic Economy 2016/2017 Report. Dubai : Thomson Reuters.______________. 2017. State of The Global Islamic Economy 2017/2018 Report. Dubai : Thomson Reuters. ______________. 2018. State of The Global Islamic Economy 2018/2019 Report. Dubai : Thomson Reuters.Todaro, Michael P. dan Stephen C. Smith. 2004. Pembangunan Ekonomi di Dunia Ketiga. Edisi Kedelapan. Jakarta : Penerbit Erlangga